Preferences of psychiatric practitioners for core symptoms of major depressive disorder: a hidden conjoint analysis. Issue 1 (9th November 2016) - Riepe, Matthias W.; Gritzmann, Peter; Brieden, Andreas
Abstract: According to ICD‐10 and DSM‐V, symptoms of depressive disorder are considered to be equally important for severity judgment. It was the goal to investigate the weight of selected symptom complexes for severity judgment. In workaday life severity judgment results from an overall impression rather than from calculating severity in different symptom complexes, separately. In fact, the drivers for overall judgment may not be known explicitly to the psychiatrist himself. A method of choice to resolve this is conjoint analysis. Based on the Montgomery–Asberg Depression Scale (MADRS) and the Sheehan Disability Scale (SDS) case vignettes were constructed. Different symptom severity in the domains mood, vegetative symptoms, cognition/inhibition, suicidality, and everyday functioning were worked into the vignettes. Different symptom complexes influence the severity judgment by clinical psychiatrists to a rather different extent. Mood has a greater impact on severity judgment than suicidality, cognition/inhibition, vegetative symptoms, and everyday functioning. We conclude that core complexes of major depressive disorder are valued with different clinical relevance by psychiatrists. Thus, diagnosis and appraisal of therapeutic efficacy are subject to individual preferences of clinical psychiatrists and prevalence and therapeutic efficacy may be over‐ or under‐estimated unless these differences in preferences are taken into account.